Sanções tributárias e sanções políticas: temas que interessam ao direito tributário - Rocha, Agamenon Suesdek da (2010)
The work herein presented is of interdisciplinary nature. It aims to study the Political Sanctions in Tax Law in the context of Brazilian Federal Constitution (1988), considering that they are one out of several tributary sanctions imposed by the Law in order to obligate a defaulter to pay taxes. Taking into account our objectives, we shall indeed follow ways which allow us to discuss concepts of Law, Legal Obligation, active debt, the use of regulatory taxes, and sanctions in tax law, making use of theories about sanctions and Law philosophical doctrines. The subject is rich of momentous aspects, either in the universe of principles or in the practical field. We shall address Sanctions in general and Political Sanctions in depth, which apparently represent hindrances created by administrative authorities in order to impede the activities of the taxpayer. As a conclusion, we pose the MATRIX NORM OF POLITICAL SANCTION / Agamenon Suesdek da Rocha, also formalised in symbolic logical language. Although the present work was primarily developed in the Constitutional level, it also addresses infra-constitutional and administrative aspects. It comprises five chapters approaching diverse kinds of violations of tax law among which the political sanctions are emphasized